The Validity Of The Additional Obligations Of The Notary Profession Through PP Number 43 Of 2015 Of The Notary As The Reporting Party - Prawati, Linda; Aprilianda, Nurini; Harini, Novitasari Dian Phra (International Journal of Business, Law, and Education, 2024)
The Indonesian government has enacted Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering, along with its implementing regulation, Government Regulation Number 43 of 2015 on Reporting Parties in the Prevention and Eradication of Money Laundering Crimes. This regulation designates Notaries as one of the reporting parties in Suspicious Financial Transactions related to Money Laundering (TFM), obligated to submit reports to the Financial Transaction Reports and Analysis Center (PPATK). Meanwhile, Article 16 paragraph (1) letter f of the Notary Law states that in carrying out their duties, Notaries must maintain the confidentiality of deed contents. Here, there is a contradiction between legal regulations. This study aims to examine and analyze the validity and legal consequences of the additional professional obligations for Notaries as stipulated in the Notary Law, supplemented by Government Regulation Number 43 of 2015, designating Notaries as reporting parties in TFM related to Money Laundering. The research indicates that the confidentiality duty of Notaries is not absolute; in other words, the obligation to maintain confidentiality in the Notary Law can be set aside by other laws, in this case, the Law on the Prevention and Eradication of Money Laundering through Government Regulation Number 43 of 2015, a directly authorized implementing regulation. The additional obligation as a reporting party cannot be considered a violation of the principle of notary confidentiality but rather a form of protection, with Minister of Law and Human Rights Regulation Number 9 of 2017 serving as an implementation of the prudence principle for Notaries in performing their duties. Furthermore, the legal consequences for Notaries, if they breach their duty as keepers of official secrets, may include criminal sanctions based on Article 322 of the Criminal Code and Law Number 43 of 2009 concerning Archives, civil sanctions under Article 1365 of the Civil Code, and administrative sanctions under Article 85 of the Notary Law. Additionally, if a Notary fails to report suspicious financial transactions resulting in criminal activities, the Notary faces the threat of punishment as regulated in Article 5 of the Law on the Prevention and Eradication of Money Laundering, which includes passive involvement in money laundering crimes (Article 55 of the Criminal Code) and active assistance in criminal activities (Article 56 of the Criminal Code).